2019
DOI: 10.3389/fncel.2019.00166
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Synaptic Strength After Mild Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) affects millions of Americans annually, but effective treatments remain inadequate due to our poor understanding of how injury impacts neural function. Data are particularly limited for mild, closed-skull TBI, which forms the majority of human cases, and for acute injury phases, when trauma effects and compensatory responses appear highly dynamic. Here we use a mouse model of mild TBI to characterize injury-induced synaptic dysfunction, and examine its progression over the hours to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 110 publications
(182 reference statements)
1
16
0
Order By: Relevance
“…5 A). Since TBI is known to lead to an imbalance in cortical excitation and inhibition [ 7 , 11 , 15 , 19 , 110 ] we predicted that the changes in synapse number suggested by the reduction in synaptophysin levels might be due to changes in the levels and ratios of excitatory glutamatergic and inhibitory GABAergic synapses. To investigate this possibility we evaluated the levels of PSD95, a marker of glutamatergic terminals [ 24 ], and of Gephyrin, a marker of GABAergic terminals [ 91 ] in the PFC of sham and injured mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A). Since TBI is known to lead to an imbalance in cortical excitation and inhibition [ 7 , 11 , 15 , 19 , 110 ] we predicted that the changes in synapse number suggested by the reduction in synaptophysin levels might be due to changes in the levels and ratios of excitatory glutamatergic and inhibitory GABAergic synapses. To investigate this possibility we evaluated the levels of PSD95, a marker of glutamatergic terminals [ 24 ], and of Gephyrin, a marker of GABAergic terminals [ 91 ] in the PFC of sham and injured mice.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, these data suggest that after rmTBI there is a temporary preferential loss of inhibitory synapses and a more robust regeneration of excitatory synapses, resulting in a temporary increase in the ratio of excitatory:inhibitory activity. A change in the balance of cortical excitatory and inhibitory activity after injury has been described by others [ 19 ] with many showing a specific loss of inhibitory synaptic activity [ 7 , 11 , 15 , 110 ]. The PSD95 and Gephyrin levels return to baseline by 1 w after rmTBI and might thereby restore the balance of excitatory and inhibitory synaptic activity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is also evidence showed that TBI could also affects the synaptic plasticity 37 . Synaptic function is rapidly disturbed after TBI 38 , and could also continue to the chronic stage 39 . Our experiment evaluates the synaptic function in the cortex and in the hippocampus of each group of mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo injuries have been modeled in rodents and provide a close approximation to the human condition. Using ex vivo brain slice analysis of in vivo injuries (as shown in Figure 1A), recent studies have shown changes in circuit excitability (11)(12)(13)(14)(15), neuro-immune interactions (16) and cell-specific changes (17,18). Our recent slice physiology studies after FPI identified a role for the innate immune receptor, toll-like receptor 4 (TLR4), in enhancing calcium-permeable AMPA receptor currents early after FPI.…”
Section: Ex Vivo Analysis Of In Vivo Injury Modelsmentioning
confidence: 99%